Per- and polyfluoroalkyl substances (PFAS) presence in food: Comparison among fresh, frozen and ready-to-eat vegetables. (1st June 2023) - Piva, Elena; Fais, Paolo; Ioime, Pasquale; Forcato, Mattia; Viel, Guido; Cecchetto, Giovanni; Pascali, Jennifer P.
Highlights: Differences in type and amount of PFAS were observed among the three groups. Ready-to eat vegetables displayed a higher PFAS content than fresh/frozen products. Organic vegetables contained a lower PFAS content than their traditional counterpart. PFOA, PFOS and PFNA were detected above the recommended attention limits. Abstract: There is a worldwide discussion to provide safety limits in food for per- and polyfluoroalkyl substances (PFAS), a group of persistent contaminants associated to human disease. Processed food is more at risk of containing increased amounts of PFAS as a consequence of intentionally or non-intentionally contamination during manipulation and packaging. Among food products, also vegetables can be submitted to industrial manipulation; therefore, a different PFAS content correlated to the level of vegetables processing is conceivable. This study assessed the amount and type of PFAS present in fresh, frozen and ready-to-eat vegetables. Differences have been observed between the three groups of samples in the average PFAS content; the difference between ready-to eat and frozen vegetables resulted statistically significative. Organic vegetables displayed a lower total amount of PFAS respect to the traditional counterpart. The impact of industrial manipulation remains to be cleared, but pesticides use during cultivation could be considered a source of PFAS contamination.